Pengaruh Kegiatan Literasi Dasar terhadap Minat Baca Siswa kelas IV SD Advent Tomohon - Jeisi Riska Merdekawati Mentu; Junita Christi Makawawa (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the effect of basic literacy on reading interest in fourth grade students at Advent Tomohon Elementary School. This research uses experimental research methods with this type of research one group pretest-posttest design with the aim of seeing the effect of students' reading interest before and after basic literacy treatment. The population in this study were all fourth-grade students at Tomohon Adventist Elementary School for the 2020 academic year. The sample in this study was 13 fourth grade students at Tomohon Adventist Elementary School for the 2020 academic year. The data collection technique in this research is by using a questionnaire instrument student reading interest questionnaire. The data analysis technique in this research uses descriptive statistical tests to see the increase in students' reading interest and t-test paired sample t-test to see the difference in students' reading interest before and after treatment. Based on the research results, it can be concluded that the reading interest of fourth grade students at Advent Tomohon Elementary School increased as evidenced by the results of the average score or mean before treatment, namely 64.38% after treatment obtained an average value or mean namely 87.53. Hypothesis via t-test usingPaired Samples T-Test shows that valuesay.(2-tailed)=0.000 < 0.05 so it can be concluded that Ho is rejected and H1 is accepted, thus it can be concluded that there is an influence of basic literacy activities on the reading interest of fourth grade students at Tomohon Adventist Elementary School